Mechanism and rates of exchange of L7/L12 between ribosomes and the effects of binding EF-G. - Deroo, S; Hyung, S; Marcoux, J; Gordiyenko, Y; Koripella, R; Sanyal, S; Robinson, C (2012)
The ribosomal stalk complex binds and recruits translation factors to the ribosome during protein biosynthesis. In Escherichia coli the stalk is composed of protein L10 and four copies of L7/L12. Despite the crucial role of the stalk, mechanistic details of L7/L12 subunit exchange are not established. By incubating isotopically labeled intact ribosomes with their unlabeled counterparts we monitored the exchange of the labile stalk proteins by recording mass spectra as a function of time. On the basis of kinetic analysis, we proposed a mechanism whereby exchange proceeds via L7/L12 monomers and dimers. We also compared exchange of L7/L12 from free ribosomes with exchange from ribosomes in complex with elongation factor G (EF-G), trapped in the posttranslocational state by fusidic acid. Results showed that binding of EF-G reduces the L7/L12 exchange reaction of monomers by ~27% and of dimers by ~47% compared with exchange from free ribosomes. This is consistent with a model in which binding of EF-G does not modify interactions between the L7/L12 monomers but rather one of the four monomers, and as a result one of the two dimers, become anchored to the ribosome-EF-G complex preventing their free exchange. Overall therefore our results not only provide mechanistic insight into the exchange of L7/L12 monomers and dimers and the effects of EF-G binding but also have implications for modulating stability in response to environmental and functional stimuli within the cell.